Optical properties of polycrystalline alumina after irradiation with iron ions and annealing; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 1, iss. 2 - Kabyshev A. V. Alexander Vasilievich (2007, 2007)
Title screen